Relationship between the Pedaling Biomechanics and Strain of Bicycle Frame during Submaximal Tests - Aneliya V. Manolova; Samuel Crequy; Philippe Lestriez; Pierre Debraux; William M. Bertucci (Sports, 2015)
The aim of this study was to analyse the effect of forces applied to pedals and cranks on the strain imposed to an instrumented bicycle motocross (BMX) frame. Using results from a finite element analysis to determine the localisation of highest stress, eight strain gauges were located on the down tube, the seat tube and the right chain stay. Before the pedaling tests, static loads were applied to the frame during bench tests. Two pedaling conditions have been analysed. In the first, the rider was in static standing position on the pedals and applied maximal muscular isometric force to the right pedal. The second pedaling condition corresponds to three pedaling sprint tests at submaximal intensities at 150, 300 and 550 W on a cycle-trainer. The results showed that smaller strain was observed in the pedaling condition than in the rider static standing position condition. The highest strains were located in the seat tube and the right chain stay near the bottom bracket area. The maximum stress observed through all conditions was 41 MPa on the right chain stay. This stress was 11 times lower than the yield stress of the frame material (460 MPa). This protocol could help to adapt the frame design to the riders as a function of their force and mechanical power output. These results could also help design BMX frames for specific populations (females) and rider morphology.